Konsep Asas Legalitas Terhadap Pengaturan Living Law dalam Pembaharuan Kitab Undang-Undang Hukum Pidana Terkait Fungsi Penuntutan oleh Kejaksaan Republik Indonesia pada Sistem Peradilan Pidana - Deviyanti, Dita (The Prosecutor Law Review, 2025)
The integration of living law in society within the concept of the principle of legality, which has been a fundamental principle for the prosecution in carrying out its prosecution function, is feared to become a "threat" that hinders the enforcement of criminal law. The contradiction between the principle of legality and living law in relation to the prosecution function by the Prosecutor's Office is the main focus of this research. The research method used in this study is normative legal research. The result of the research is that the principle of legality is one of the fundamental principles in the implementation of prosecution by the Prosecutor's Office. This principle provides clear guidance to the prosecution in carrying out its prosecution function, specifically the authority of the prosecution in drafting indictments that should be based on the formulation of provisions in the laws violated by the defendant. The indictment must be precise, clear, and complete and in accordance with the elements of the crime regulated in the law. However, in relation to the implementation of living law based on Article 2 paragraph (1), prosecution by the Prosecutor's Office should carefully consider the living law in society, because some customary laws still play a central role in resolving disputes and the need for technical rules to avoid errors in the application of living law for all law enforcement elements, including the prosecution.